2016
DOI: 10.1111/anae.13577
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing two popliteal nerve catheter tip positions for postoperative analgesia after day‐case hallux valgus repair

Abstract: We compared the effect of two different positions of a sciatic nerve catheter within the popliteal fossa on local anaesthetic consumption and postoperative analgesia in patients undergoing day-case hallux valgus repair. Eighty-four patients were randomly allocated to receive a sciatic nerve catheter either between the tibial and peroneal components (sciatic group) or medial to the tibial nerve (tibial group). The primary endpoint was postoperative local anaesthetic consumption, while secondary endpoints were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Hauritz et al 222 found that, compared to its out-of-plane (OOP) counterpart, the IP technique was associated with a fourfold increase in catheter dislodgement and 150% greater opioid (morphine) requirements. A recent trial (n=82) compared positioning the catheter tip between the tibial and peroneal nerves or medial to the tibial nerve in the subparaneural space 223. Catheter tip placement medial to the tibial nerve resulted in lower incidences of foot drop (p=0.012) and insensate limb (p<0.001) without impacting overall analgesia and LA consumption 223…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 99%
“…Hauritz et al 222 found that, compared to its out-of-plane (OOP) counterpart, the IP technique was associated with a fourfold increase in catheter dislodgement and 150% greater opioid (morphine) requirements. A recent trial (n=82) compared positioning the catheter tip between the tibial and peroneal nerves or medial to the tibial nerve in the subparaneural space 223. Catheter tip placement medial to the tibial nerve resulted in lower incidences of foot drop (p=0.012) and insensate limb (p<0.001) without impacting overall analgesia and LA consumption 223…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 99%
“…The results of the literature search are summarised in Figure 1 . Thirty-one articles met the inclusion criteria and were included in this systematic review [ 12 42 ]. A detailed description of the pain outcomes utilised and timings of measurements in the included studies is provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (27/31) utilised two or more pain outcomes. The most commonly used outcome measures were numerical grading of pain/numerical reporting scale (NRS) out of 10 (16 studies) [ 12 , 17 , 20 24 , 27 29 , 32 – 35 , 38 , 40 ], opioid consumption (16 studies), and visual analogue scale 10 cm (VAS; 12 studies) [ 13 16 , 25 , 26 , 31 , 36 , 37 , 39 , 41 , 42 ]. Other than reporting total opioid consumption, analgesia usage was also measured with the following outcomes: nonopioid analgesic requirement [ 14 , 16 , 32 , 33 , 36 ], total supplementary analgesic requirement [ 34 , 35 ], and cumulative opioid consumption [ 26 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, peripheral nerve blockade has been to play the major role in postoperative multimodal pain regimens . The conventional nerve block techniques for forefoot surgery are popliteal sciatic nerve block or ankle nerve blocks . The technique of popliteal sciatic nerve block has better analgesic effect than subcutaneous infiltration in foot surgery, but popliteal sciatic nerve block may impair immediate postoperative ambulance and is associated with common peroneal nerve damage or residual sensory dysfunction; therefore, blocking the distal braches of the sciatic nerve that provide comprehensive coverage of the area related to HV correction surgery while preserving the motor function of ankle should be considered.…”
Section: Discussionmentioning
confidence: 99%